Membangun Kesiapan Kerja Mahasiswa Ditinjau Dari Pelatihan, Dukungan Sosial Dan Efikasi Diri - Mitra, Tia; Attiq, Khoirul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The aim of this research is to evaluate whether training and social support have an impact on work readiness, with self-efficacy as an intervening variable. The research population includes undergraduate students in Semarang city who have participated in competency training, with a sample size of 94 students selected through purposive sampling using the Slovin formula. Data was collected through a survey using a questionnaire instrument. The results of this study indicate that : (1)Training (X1) has a significant positive effect on work readiness (Y), (2) Training (X1) also has a positive effect on self-efficacy (Z), (3) Self-efficacy (Z) has a positive effect on work readiness (Y), (4) Social support (X2) does not have a significant effect on work readiness (Y), (5) Social support (X2) has a positive effect on self-efficacy (Z), (6,7) Furthermore, the test of indirect effects indicates that self-efficacy (Z) positively mediates the relationship between training (X1) and work readiness (Y), as well as the relationship between social support (X2) and work readiness (Y).